Impact of sales promotion and product quality on zoya customer purchase interest - Rina, Rina Amalia Putri; Lusianti, Dina; Faidah, Faridhatun (Journal of Student Research Exploration, 2024)
This research analyses the influence of Sales Promotion and product Quality on Purchase Interest through Brand Awareness. This is a significant concern because product quality is an important thing that every company must strive for if it wants to compete in the market. The object of this research is Zoya Kudus. The sampling technique used purposive sampling with the rule of thumb formula to produce a sample of 120. The analysis tool in this research used SEM-AMOS. This research shows that Sales Promotion and Product Quality have a positive and significant effect on Brand Awareness. Sales Promotion and product quality have influenced purchase Intention. Sales promotion on purchasing interest through brand awareness influences partial mediation. Product quality on purchase intention through brand awareness has a mediating influence, but the influence is weak.